Primary esophageal tuberculosis: A case report - Vengoa Humpire, Rosmeri (2021)
A 60-year-old woman born in Tarma and living in Lima, with a history of biomass exposure, contact with a patient with tuberculosis, arterial hypertension, heart arrhythmia and mother with ovarian cancer, visited the medical center with progressive dysphagia, 15-kilogram weight loss and evening fever for seven months. A previous endoscopy revealed an esophageal tumor. A CT scan showed middle and distal third esophageal wall thickening, and 10x10 mm mediastinal adenopathies. The rest of the thoracic and abdominal organs were normal. The last endoscopy revealed an ulcerated lesion in the esophagus. The pathological evaluation showed a large chronic granulomatous inflammation with giant cells and necrosis. Ziehl–Neelsen stain was negative for Koch bacillus and revealed no malignant lesion. A Mycobacterium tuberculosis-positive polymerase chain reaction (PCR) was observed. An adenopathy biopsy was performed by endoscopic ultrasound and PCR outcome was negative for Mycobacterium tuberculosis. In conclusion, primary esophageal tuberculosis was diagnosed and a specific treatment with a weight-adjusted dose was initiated.